2004
DOI: 10.1259/bjr/51474597
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocele of the canal of Nuck in a girl: ultrasound and MR appearance

Abstract: Hydrocele of the canal of Nuck is a rare condition in females. A small evagination of parietal peritoneum forms the canal of Nuck. Failure of complete obliteration of the canal results in either an indirect inguinal hernia or a hydrocele of the canal of Nuck. We present a case in a 7-year-old girl. On ultrasound, there was a comma-shaped cyst with the tail directed cranially toward the inguinal canal. The cyst had no internal echoes and demonstrated increased through transmission. Coronal and axial MR showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 0 publications
0
69
0
1
Order By: Relevance
“…It is the female equivalent of the processus vaginalis testis in males which extends along the testes in the descent from the lumbar region to the scrotum. Normally, it undergoes complete obliteration during the first year of life [1]. Incomplete obliteration creates a potential passageway for indirect inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is the female equivalent of the processus vaginalis testis in males which extends along the testes in the descent from the lumbar region to the scrotum. Normally, it undergoes complete obliteration during the first year of life [1]. Incomplete obliteration creates a potential passageway for indirect inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [1,2] have described a comma-shaped tail extending from the lesion into the inguinal canal, while others describe the appearance as ''a cyst within the cyst'' [3] or a cystic mass with thin multiple septa [4,5]. The graded compression technique allows observation of a fluid-filled canal which connects the cyst with the abdominal cavity [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anderson et al [1] found a tubular anechoic mass extending along the course of the round ligament without any internal structures, thus representing a unilocular hydrocele. Park et al [5] described a cystic structure with a comma shaped tail directed towards the inguinal canal. The reported case was a cystic, thin-walled structure in the inguinal area with hypointense T1 signal and hyperintense T2 signal characteristics; it was the first report of MRI findings in this pathology in English literature.…”
Section: Discussionmentioning
confidence: 99%